Trophoblast stem cells, trophoblast invasion, and organoids - advancements in gynecology - Gašparová, Petra; Ballová, Zuzana; Bačenková, Darina; Trebuňová, Marianna; Dosedla, Erik (Ceska gynekologie, 2024)
The human placenta serves as a vital barrier between the mother and the developing fetus during pregnancy. A defect in the early development of the placenta is associated with severe pregnancy disorders. Despite its complex development, various molecular processes control placental development, and the specialization of trophoblast cells is still not fully understood. One primary obstacle is the lack of suitable cell model systems. Traditional two-dimensional (2D) cell cultures fail to mimic in vivo conditions and do not capture the intricate intercellular interactions vital for studying placental development. However, three-dimensional (3D) organoid models derived from stem cells that replicate natural cell organization and architecture have greatly improved our understanding of trophoblast behavior and its medicinal applications. Organoids with relevant phenotypes provide a valuable platform to model both placental physiology and pathology, including the modeling of placental disorders. They hold great promise for personalized medicine, improved diagnostics, and the evaluation of pharmaceutical drug efficacy and safety. This article provides a concise overview of trophoblast stem cells, trophoblast invasion, and the evolving role of organoids in gynecology.
Keywords: Organoids; Trophoblasts; Pregnancy complications; Pregnancy; těhotenství; Placenta; trofoblasty; Placentation; organoidy; Stem Cells; placenta; lidé; ženské pohlaví; trophoblast invasion; Humans; placentace; trophoblast stem cells; Female; kmenové buňky